Data encryption based on 7D complex chaotic system with cubic memristor for smart grid - Kou, Lei; Huang, Zhe; Jiang, Cuimei; Zhang, Fangfang; Ke, Wende; Wan, Junhe; Liu, Hailin; Li, Hui; Lu, Jinyan (Frontiers in Energy Research, 2022)
At present, the smart grid (SG) has become an indispensable part of infrastructure all over the world. In order to avoid the malicious attack and ensure the information security, the cryptographic techniques are essential. This paper focuses on the encryption techniques to ensure the information security of SG. Firstly, a novel 7D complex chaotic system with cubic memristor is proposed. And its attractors, Lyapunov exponent, bifurcation diagram, complexity and 0-1 test are analyzed. Secondly, based on the proposed complex chaotic system, a designed algorithm is proposed to ensure the encryption security. Finally, the proposed encryption scheme is verified with data and monitoring images in SG, and the security analysis are provided. The verification results show the proposed encryption scheme is technically feasible and available for data and image encryption in SG. And it can ensure the information security of SG.